Early Detection of Risk Factor for Suicidal Ideation Among Senior High School Students in Jakarta: Updated Measurement - Yusuf, Nova R; Prasetyo, Sabarinah; Good, Byron J (Kesmas, 2024)
The key strategy to address suicide in adolescents is school-based suicidal prevention by adapting a screening instrument to the local culture and policymakers’ perception of suicide. This study aimed to develop an instrument for the early detection of risk for suicidal ideation and identify influential risk factors for suicidal ideation among high school students in Jakarta, Indonesia. This study was conducted in 2018 with a mixed-method design (quantitative and qualitative approaches). It was found that 5% of students had suicidal ideation in July–November 2018, and 13.8% had a high-risk factor for suicidal ideation. The instrument developed in this study consisted of 16 items and had been proven valid and reliable for screening. Students with depression and those screened positive utilizing the developed instrument had 4.41 and 5.39 times the risk of developing suicidal ideation. A recommendation to the counseling teacher associations is to reduce suicidal stigma, encourage students to be open to talking about mental health issues, and prioritize adolescents at risk of suicide for further assessment.